Characterising southern ocean phytoplankton community variability and environmental coupling: zonal, sectoral, and seasonal perspectives - Quinlan, Liam Bodley (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.